Papel dos receptores P1 e da cafeína na proliferação de carcinoma de células escamosas de esôfago - Abreu, Bianca Regina Ribas de (2014)
Esophageal cancer is the eighth most common cancer worldwide. The prognosis for this cancer is poor, generally, the overall survival rate is 10-15% with about five years of survival. Adenosine is present in different tissues of various organisms and plays an extremely important role in the purinergic system. Adenosine is produced directly or indirectly by ATP and its target P1 receptors which are G-protein coupled (A1, A2A, A2B and A3). Caffeine is a non-selective adenosine antagonist and has low affinity for A3 great affinity for A1, A2A and A2B. The objective of this study was to investigate the role of P1 purinergic receptors and the action of caffeine on the proliferation of squamous cell carcinoma of the esophagus, using the human lineage of squamous cell esophageal OE21. First we demonstrated that P1 receptors are expressed in the cell line by means of qRT-PCR and still A2A receptor expression was significantly reduced when these cells were treated with caffeine (100 μM). In addition to the caffeine treatment also decreases cell proliferation (1, 5 e 10 mM) and this effect was most likely a type of non-apoptotic cell death. Similarly, adenosine decreases cell viability (1, 5 and 10 mM) and proliferation (5 mM) via apoptosis and dipyridamole (10 μM) affect cell viability and did not alter the type of death caused. These results demonstrate the in vitro investigation of adenosine and caffeine in esophageal cancer receptors and this is a first step to understanding of purinergic signaling in esophageal cancer.